2021
DOI: 10.1007/s10461-021-03353-2
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for the Design of Pre-exposure Prophylaxis (PrEP) Interventions for Women: Lessons Learned from the Implementation of a Novel PrEP Intervention

Abstract: Pre-exposure prophylaxis (PrEP) uptake among women in the United States has been low. To increase uptake, we developed a peer outreach and navigation PrEP intervention. Semi-structured qualitative interviews with 32 cisgender women and 3 transgender women were conducted to assess the intervention. We used a thematic approach to identify barriers to, and facilitators of the intervention. Facilitators included interest in PrEP, offer of health and social services, the intervention’s women-focused approach, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 84 publications
2
16
0
Order By: Relevance
“…Yet, once aware and knowledgeable about PrEP, PWID are interested in taking it [ 5 , 107 ]. Similar to other studies, participants in this study described perceived low HIV risk as a reason for not being interested in taking PrEP [ 108 ]. Although participants may have accurately described their risk, past research has shown that perceived HIV risk does not always match actual risk [ 34 ] and a recent study found that 92% of PWID sampled in Massachusetts met CDC indications for PrEP [ 109 ].…”
Section: Discussionsupporting
confidence: 77%
“…Yet, once aware and knowledgeable about PrEP, PWID are interested in taking it [ 5 , 107 ]. Similar to other studies, participants in this study described perceived low HIV risk as a reason for not being interested in taking PrEP [ 108 ]. Although participants may have accurately described their risk, past research has shown that perceived HIV risk does not always match actual risk [ 34 ] and a recent study found that 92% of PWID sampled in Massachusetts met CDC indications for PrEP [ 109 ].…”
Section: Discussionsupporting
confidence: 77%
“…As a result, the authors recommended embedding PrEP in the latter, alongside peer- and structurally competent interventions. 18 …”
Section: Discussionmentioning
confidence: 99%
“… 6 , 17 In the United Kingdom, gay and bisexual men considered peer support from friends and partners who used PrEP essential, ‘ less abstract ’ and ‘ more trustworthy ’ than general information about PrEP. 17 In the United States, qualitative assessment of a PrEP intervention for cis and trans women found its ‘ women-focused approach ’ and ‘ peer outreach and navigation ’ to be key factors facilitating uptake 18 (pp. 3987).…”
Section: Introductionmentioning
confidence: 99%
“…Such studies would categorize by gender rather than sex assigned at birth and would better represent gendered dynamics of individuals’ social ecologies that shape their health behaviors and experiences. Examples of such research can be found in some implementation strategies and interventions trials, including Walters et al’s ( 2021 ) implementation of a PrEP intervention for cisgender and transgender women and Auerbach et al’s ( 2021 ) interviews with cisgender and transgender women on developing HIV care for all women. It must be noted, though, that limited sub-samples of transgender individuals within samples lumping cisgender MSM and transgender women is not unique to implementation science.…”
Section: Discussionmentioning
confidence: 99%